Neurologic Outcomes After Extracorporeal Cardiopulmonary Resuscitation: Recent Experience at a Single High-Volume Center. Issue 2 (21st April 2021) - Podell, Jamie E.; Krause, Eric M.; Rector, Raymond; Hassan, Mubariz; Reddi, Ashwin; Jaffa, Matthew N.; Morris, Nicholas A.; Herr, Daniel L.; Parikh, Gunjan Y.
Abstract : Supplemental Digital Content is available in the text. Abstract : Extracorporeal cardiopulmonary resuscitation (ECPR)—veno-arterial extracorporeal membrane oxygenation (ECMO) for refractory cardiac arrest—has grown rapidly, but its widespread adoption has been limited by frequent neurologic complications. With individual centers developing best practices, utilization may be increasing with an uncertain effect on outcomes. This study describes the recent ECPR experience at the University of Maryland Medical Center from 2016 through 2018, with attention to neurologic outcomes and predictors thereof. The primary outcome was dichotomized Cerebral Performance Category (≤2) at hospital discharge; secondary outcomes included rates of specific neurologic complications. From 429 ECMO runs over 3 years, 57 ECPR patients were identified, representing an increase in ECPR utilization compared with 41 cases over the previous 6 years. Fifty-two (91%) suffered in-hospital cardiac arrest, and 36 (63%) had an initial nonshockable rhythm. Median low-flow time was 31 minutes. Overall, 26 (46%) survived hospitalization and 23 (88% of survivors, 40% overall) had a favorable discharge outcome. Factors independently associated with good neurologic outcome included lower peak lactate, initial shockable rhythm, and higher initial ECMO mean arterial pressure. Neurologic complications occurred in 18 patients (32%), including brain death in 6 (11%), hypoxic-ischemic brain injury in 11 (19%), ischemic stroke in 6 (11%), intracerebral hemorrhage in 1 (2%), and seizure in 4 (7%). We conclude that good neurologic outcomes are possible for well-selected ECPR patients in a high-volume program with increasing utilization and evolving practices. Markers of adequate peri-resuscitation tissue perfusion were associated with better outcomes, suggesting their importance in neuroprognostication.